Identification and Characteristics of Actinomycetes Useful for Semicontinuous Treatment of Domestic Animal Feces - Hayashida, Shinsaku (1988)
Selected strains of actinomycetes useful for practicing semicontinuous treatment of swine and poultry feces were identified as Streptomyces antibioticus S-4, S. puniceus N-50-2, S. nigrifaciens N-9-3, Thermoactinomyces vulgaris HIR-60, and Thermomonospora viridis HIR-50. These five obligately aerobic strains grew preferably on nonsterilized fresh swine feces in 24 h without any additives. They assimilated offensive volatile fatty acids in the swine and poultry feces. Cultures of these five strains were mixed and used as seed for the practical treatments of 1 ton of swine feces over the wide temperature range of 15 to 60°C. Strain HIR-50 grew most predominantly on both fresh swine and poultry feces at 50 to 55°C and decomposed uric acid. For the efficient penetration of mycelia into the feces, manures were mixed once a day so as not to break the solid mass, and the dehydration rate of feces had to be controlled in proportion to the mycelial growth rate. The actinomycete biofertilizer thus manufactured in 10 days was odorless and promotive of plant growth.